Dual Benefits of Enhanced Oil Recovery and CO2 Sequestration: The Impact of CO2 Injection Approach on Oil Recovery - Alam, Mir Muhammad Mansoor; Hassan, Amjed; Mahmoud, Mohamed; Sibaweihi, Najmudeen; Patil, Shirish (Frontiers in Energy Research, 2022)
Injection of CO2 to enhance oil recovery is widely used due to its multiple advantages such as mobilizing the oil and sequestration of carbon dioxide. Injection of CO2 can enhance oil recovery by reducing the oil viscosity and improving overall mobility. However, several problems are associated with CO2 injection such as viscous fingering, gravity override, and CO2 channeling that results in early gas breakthrough, low sweep efficiency, and low ultimate oil recovery. In this study, a new approach of dual benefits of enhancing the oil recovery and sequestering the carbon dioxide is presented. In this work, different scenarios of field scale simulation were conducted to evaluate the oil recovery during CO2 injection, using CMG (Computer Modeling Group) software package. Three main scenarios were examined in this work; CO2 injection into the reservoir, CO2 injection into the aquifer, and CO2 injection into the aquifer followed by waterflooding. Also, three well configurations were utilized which are; all injectors and producers are drilled vertically, all wells are drilled horizontally, and vertical injectors and horizontal producers. Therefore, the reservoir performance was examined for nine scenarios over a 20-year period. In all simulated models, the CO2 injection was started at the residual oil saturation (Sor) conditions, to represent the depleted oil reservoirs. The results indicated that the highest oil recovery of 73% of the original oil-in-place (OOIP) can be achieved by injecting CO2 into the reservoir, utilizing vertical injectors and producers. While injecting CO2 into aquifers can significantly enhance the oil recovery by around 68-70% of the OOIP. Also, using horizontal wells can provide more oil recovery (67.7%) compared to using vertical wells (54.8%), in the same conditions. Finally, CO2 injection outperformed conventional water flooding, where 68% against 12% of the OOIP were obtained, respectively. Overall, injection of CO2 into the depleted reservoir can provide dual benefits of CO2 sequestration and improved oil recovery. CO2 can be injected into the water zone resulting in a slow release of CO2 which will reduce the fluid viscosity, enhance oil recovery, and reduce the greenhouse effect.